Technical appendix: Tax laws and revenue effects - Sascha Mierzwa (Philipps-University Marburg, School of Business and Economics, 2021)
This documentation extends Romer and Romer's (2009), Cloyne's (2012), Uhl's (2012), and Gechert et al.'s (2016) narrative accounts of legislated tax changes up to the end of 2017. The dataset is the basis of my PhD dissertation (Hayo & Mierzwa, 2020, 2021a, 2021b, 2021c; Hayo et al., 2021; Mierzwa, 2021).
Keywords: 330